THE IMPACT OF EXPECTATIONS ON THE MENTAL HEALTH OF YOUNG BRIDES AND GROOMS (European Journal of Interdisciplinary Research and Development, 2026)
This article analyzes the impact of social, familial, and cultural pressures encountered in the lives of young brides and grooms on their mental health. In particular, it highlights the psychological effects of various demands and “expectations” imposed by relatives, society, and traditional views, such as responsibility, early childbearing, economic stability, and adaptation. The article examines the causes of mental states such as stress, anxiety, and depression, as well as ways to prevent them from both scientific and practical perspectives. In addition, the importance of mutual understanding, psychological preparedness, and social support in forming a healthy family environment is substantiated.